L’eau potable pourrait-elle devenir un bien commun ? - Rémi Barbier; Bernard Barraqué; Cécile Tindon (Développement Durable et Territoires)
In France, the hegemony of drinking water considered as a commodity has been disputed for two to three decades by a rather heterogeneous set of associations and coalitions supporting its replacement by an alternative conception, that of drinking water as a “common good”. This reference is sometimes put forward as a simple standard, supposed to impose itself with the sole force of evidence. Taking it seriously, we develop a cross-disciplinary prospect on a possible conception of drinking water as a common good. After showing the difficulty to use either the institutional economic framework or the “right to water” approach, we explore an anthropologic perspective based on the notion of “coexistent space”.